Study of induced systemic resistance in tomato against Fusarium oxysporum f. sp. lycopersici causing wilt of tomato - MANIKA SHARMA, P.P. JAMBHULKAR; PRATIBHA SHARMA, M. RAJA, R. THAVA PRAKASA PANDIAN (Indian Phytopathology, 2016)
Mycoparasitism is one of the key ability of Trichoderma spp. which resulted as biocontrol agents against major phytopathogens. Wilt of tomato is a major disease caused by Fusarium oxysporum f.sp. lycopersici (FoL), leads to significant yield losses of crops. The following treatments were conducted under the glass house conditions for examining the effect of salicylic acid (SA) and Trichoderma harzianum (Th3) against FoL, viz., Th3 alone, FoL alone, combination of FoL+ Th3, combination of FoL+ SA and FoL+ Th3 + SA. Significant results were found in the treatment with FoL + Th3 + SA and higher range phenol (127.6 mg), polyphenol oxidase (2.56 mg) and peroxidase (3.36 mg) production were observed. Among different concentrations of SA (0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 mM) tested, 2 mM was found to be effective against FoL by the increased production of phenol, peroxidase and polyphenol oxidase. For treatment of FoL infected plants combined application of SA (2.0 mM) and Th3 were shown the significant production of defence enzymes and promote the root and shoot length.